Total quality management (TQM) : principles, methods, and applications - Luthra, Sunil; Garg, Dixit; Agarwal, Ashish; Mangla, Sachin K. (Boca Raton : CRC Press, 2020)
"This textbook provides the understanding of all aspects of TQM and the implementation. This textbook covers all aspects of TQM, discusses quality systems in detail, highlights the importance of the needs of the customer, and presents the concept of Total Productive Maintenance (TPM)"--
OCLC-licensed vendor bibliographic record.
Keywords: Total quality management -- Textbooks; Total productive maintenance -- Textbooks; TECHNOLOGY / Manufacturing; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Industries / Manufacturing Industries